Workplace gender equality in the post-pandemic era: Where to next?. (September 2021) - Foley, Meraiah; Cooper, Rae
The COVID-19 pandemic exposed and accelerated many gendered labour market inequalities in Australia and around the world. In this introduction to our special issue, 'Workplace Gender Equality: Where are we now and where to next?', we examine the impact of the pandemic on women's employment, labour force participation, earnings, unpaid care work and experience of gendered violence. We identify five key areas where action is urgently required to create a more equitable post-pandemic recovery: addressing gender-based labour market segregations and discrimination; building access to mutually beneficial flexibility; ensuring a more gender-equitable distribution of unpaid care; confronting gender-based violence at work and beyond; and mobilising union action through gender equality bargaining.